Chiral-induced enhanced electrocatalytic behaviour of cysteine coated bifunctional Au–Ni bilayer thin film device for water splitting application - Bhartiya P.K.; Srivastava M.; Mishra D. (My University, 2025)
Designing smart electrodes is the key to the efficient water splitting for the production of large scale hydrogen as a clean energy source. In this study, we prepare an organic chiral molecule modified Au–Ni bilayer thin film electrode to examine the chiral induced spin selectivity (CISS) effect on water splitting. Electrodes with bilayer configuration consisting of thin Ni layer (100 nm) with an Au over layer (10 nm) are prepared on glass substrates by combined sputtering, thermal evaporation techniques. Subsequently, self-assembled monolayer of chiral L-Cysteine molecule is immobilized on the as-prepared Ni/Au surface by chemisorption method. The electrocatalytic behaviour of as-modified chiral electrodes (Ni/Au/Cys) has been investigated in 0.1 M KOH solution. Our results show that for achieving the current density of 5 mAcm−2 the reaction over potential decreases by 390 mV while 5-fold increase in the current density value is achieved at a fixed over potential with chiral Ni/Au/Cys thin film compared to the achiral (bare) bilayer Ni/Au thin film during oxygen evolution reaction (OER). The dramatic reduction of over potential for OER has been attributed to the spin specific reaction occurring at the chiral Ni/Au/Cys electrodes during water splitting. On the other hand, we observe that there is a decrease of 260 mV over potential with more than 11-fold increase in the absolute current density value (∼153 mAcm−2 at −0.6 V) for Ni/Au/Cys thin film than bare Ni/Au thin film in hydrogen evolution reaction (HER). The excellent bifunctional catalytic property of Ni/Au/Cys has been attributed to the synergistic effect of chirality and bilayer configuration present in the primary structure of cysteine molecule and Ni/Au thin films respectively. © 2021 Hydrogen Energy Publications LLC